EFL Pre-service Teachers’ Perceptions towards the Use of CALL in the English Language Classrooms - James Hoffman, Peter; Tachaiyaphum, Nutthida (Asian Journal of Interdisciplinary Research, 2018)
This study aimed to investigate English as a Foreign Language (EFL) pre-service teachers’ perceptions towards the use of Computer Assisted Language Learning (CALL) in the English Language Classrooms concerning the teachers’ computer competence and their perceptions of CALL after creating and using their own CALL in language teaching. The participants were EFL pre-service teachers studying in the faculty of education, Mahasarakham University, Thailand. Questionnaires were used to collect the data after teaching with CALL. The findings revealed that the overall computer competence of the participants was a moderate to a high level, yet the participants were not competent in accessing the different types of information and CALL materials online. Furthermore, the participants reported that the use of a computer made language learning interesting and encouraging. However, they demonstrated that a computer training program was required due to the lack of competence in operating some computer programs as well as the inadequate knowledge of new technology for the language learning. It can be surmised that though the EFL pre-service teachers have learned about CALL, they still find the CALL knowledge gained from the teaching methodology courses insufficient for effective CALL integration and design. Therefore, the study suggests that in order to improve teacher preparation courses, the knowledge of CALL including what CALL is, various types of CALL, as well as CALL materials evaluation be provided. Additionally, the understanding of teaching approaches should also be improved along with the technological skills since the knowledge of CALL solely is inadequate to make effective teaching. The teachers need the capability of selecting the right CALL materials and teaching approaches which are appropriate to the lesson.